Wisdom in Ugarit and in the Ancient Near East with Particular Emphasis on Old Testament Wisdom Literature - Khanjian, J. (1974)
Dissertation; Cf. Dissertation Abstracts International 35 (1974-75); order no. 74-14, 883.